2013
DOI: 10.1007/s10597-013-9605-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Poor Mental Health Status Among Homeless Women With and Without Dependent Children

Abstract: The purpose of this study was to estimate the prevalence of mental health problems among a representative sample of homeless women with and without dependent children and determine if the effects of risk factors for mental health are modified by the presence of dependent children. Homeless women (n=522) were recruited in 2004-2005 from shelters and meal programs in Toronto, Canada. Linear and logistic regression was performed to identify factors associated with mental health status. Poor mental health was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 36 publications
5
35
2
6
Order By: Relevance
“…31 Together with previous work, these findings suggest that homeless families are a distinct population who are overall healthier and may have less need for health services, perhaps reflecting a lower burden of physical and psychiatric illness. 32 Alternatively, homeless families may have been recruited into our study during a period when they were experiencing temporary or episodic homelessness and may not have been exposed to the same degree of physical, mental/emotional and social stressors as their single adult counterparts experiencing chronic homelessness. 9,33 However, the inverse association between family status and hospitalization remained significant even after adjusting for predisposing, enabling and need factors, suggesting the presence of other, possibly unmeasured, factors that may confound this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…31 Together with previous work, these findings suggest that homeless families are a distinct population who are overall healthier and may have less need for health services, perhaps reflecting a lower burden of physical and psychiatric illness. 32 Alternatively, homeless families may have been recruited into our study during a period when they were experiencing temporary or episodic homelessness and may not have been exposed to the same degree of physical, mental/emotional and social stressors as their single adult counterparts experiencing chronic homelessness. 9,33 However, the inverse association between family status and hospitalization remained significant even after adjusting for predisposing, enabling and need factors, suggesting the presence of other, possibly unmeasured, factors that may confound this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Substance abuse is not uncommon with studies indicating that 28% to 50% of homeless mothers report using illicit drugs within one year of the assessment (e.g., Hanrahan et al, 2005; Weinreb et al, 2006). Chambers et al (2014) found that homeless women with dependent children were more likely to have physical and mental health problem, as well as alcohol or drug use problems, compared to homeless women without dependent children. More frequent drug and alcohol use has been shown to predict higher rates of future intimate partner violence (El-Bassel et al, 2005).…”
mentioning
confidence: 93%
“…Briefly, mothers were on average 27.86 years old at the time of interview (range 17-41) with eight of the 14 mothers being younger (under 25), five of the mothers being 21 or younger and one being a teenager. Mothers were on average 21.29 years old when they gave birth to their first child (range [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], with 50% of mothers reporting their first pregnancy during their teenage years. The majority experienced homelessness prior to falling pregnant (64%) and, importantly, over half had experienced at least seven different episodes of homelessness since giving birth to their first child (57%).…”
Section: Participants and Proceduresmentioning
confidence: 99%